Decolonizing Human Behavior in the Social Environment: A Reader for an Anti-Oppressive Approach - Aguilar, Jemel; Carpenter, Elisabeth Counselman (Cognella Academic Publishing, 2021)
Decolonizing Human Behavior in the Social Environment: A Reader for an Anti-Oppressive Approach challenges the socialization of preservice social workers by examining the complex features of individuals, families, groups, and societies and how they present themselves within the context of the multiple and simultaneous influences on behavior, cognitions, and emotions.This text is divided into three distinct units. Unit I development at the individual level and the influences that shape human behavior, including adverse childhood experiences, identity development through social media, resilience, and chronic illness. Unit II focuses on interpersonal dynamics with articles that explore grief theories, the transgender experience, intergenerational trauma, privilege, and more. Unit III examines structural social systems such as institutional racism, religious-based prejudice, and structural violence.Written to help social work students and professionals begin the process of decolonizing their education and practice, Decolonizing Human Behavior in the Social Environment is an essential and timely reader for courses and programs in social work. It is also an exemplary resource for practitioners at all levels.
Keywords: dept.swk

‘The mirage of action’: Exploring the social work professions’ perpetuation of white supremacy through ‘Well-Intentioned’ actions - Aguilar, Jemel P.; Counselman-Carpenter, Elisabeth (Advances in Social Work, 2021)
This autoethnographic study highlights complex strategies for maintaining white supremacy used by “well-intentioned” heterocentric white female social workers that are enacted under the guise of practicing anti-racism in social work practice settings, classroom environments, policy initiatives, and advocacy work. Using autoethnography was both unplanned and deliberate. Unplanned, we needed a research method that allows us to explore the untouchable subject of heterocentric white female social workers and deliberate in that we could use our experiences to break ground and establish white supremacy among heterocentric white female social workers that espouse anti-racist values as an area of study. We draw on education, anthropology, sociology, and other disciplines to name some of the ongoing challenges to dismantling racism, colonialist, and reformer narratives in social work, and identify strategies used by all white folx, but particularly heterocentric white female social workers to neutralize the suggestion or accusation of their acts as racism. We name three challenges to dismantling racism among heterocentric white female social workers: hiding behind the data, anti-racist book clubs, and crying and comfort. We conclude with further questions for those who hold power in the field and a reflection upon our own continued intersecting struggles with these concepts. © 2021 Authors,.
Keywords: dept.swk; peer-reviewed